Social capital and mental health issues in the Nigerian environment - Ugiagbe, Ernest Osas; Okaka, Emmanuel (Journal of Nursing, Social Studies and Public Health, 2014)
Social capital is an integral part of group dynamism and individual fulfilment as members of the human society. There is now increasing evidence as to the role played by social factors in the contribution to genesis and manifestations of mental health in modern society. This paper focuses on the importance of social capital in the socio-psychological and economic wellbeing of Nigerians. The paper specifically explores and examines the nexus between the social capital base of the individuals in the society and the levels of the incidences of mental/health problems in Nigeria. The paper examines the correlates with the size and complexity of an individual’s social network, the spatial distance between an individual and the social world. Many Nigerians today are going through mental trauma occasioned by the harsh economic realities and breakdown of socio-cultural fabrics of the society and these have a far reaching impact on the mental health of Nigerians. The policy implication of this situation is discussed at the end of the paper.
Keywords: Social Capital; Cross-Cultural Comparison; Nigeria; Social Values; Social Networking; Nigérie; Social Stigma; sociální kapitál; duševní zdraví; sociální sítě; společenské stigma; sociální hodnoty; Humans; srovnání kultur; lidé; Mental Health